2016
DOI: 10.1080/14786435.2016.1177223
|View full text |Cite
|
Sign up to set email alerts
|

Scaling properties of three-dimensional random fibre networks

Abstract: Random fibre networks have unique mechanical properties and appear as the primary building blocks of many biological and structural materials. Although fibre networks are usually three-dimensional in nature, prior studies have mainly used simplistic two-dimensional models to characterize their properties. The present study creates a 3D strain-based nonaffinity measure and investigates the mechanical behaviour and scaling properties of 3D fibre networks. This measure is used to fully examine the influence of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Based on previous studies, we can state that 2D fiber network models are useful tools for gaining a general idea about the behavior of real 3D networks. For instance, in a recent study, we extended the Mikado model to 3D in order to characterize the differences and similarities between the mechanical behavior of 2D and 3D network models [29,30]. We found that the degree of nonaffinity has a power-law dependence on probing length scale in both models.…”
Section: Resultsmentioning
confidence: 88%
“…Based on previous studies, we can state that 2D fiber network models are useful tools for gaining a general idea about the behavior of real 3D networks. For instance, in a recent study, we extended the Mikado model to 3D in order to characterize the differences and similarities between the mechanical behavior of 2D and 3D network models [29,30]. We found that the degree of nonaffinity has a power-law dependence on probing length scale in both models.…”
Section: Resultsmentioning
confidence: 88%
“…As described previously, the present model shows initial strain-softening followed by a significant increase in K of several orders of magnitude. The differential modulus scales as power-law with the stress K ~ σ ν⩾1 over the strain hardening-phase, a typical behavior of semiflexible fiber networks [47,[52][53][54]. The SRG model also shows an almost initial linear response followed by a strain-hardening region, but the scaling has a smaller exponent ν ~ 1 compared to ν ~ 1.5 of the present model.…”
Section: Homogenized Response To Shear Deformationmentioning
confidence: 48%
“…The shift to the strain-hardening phase occurs earlier with increasing volume fraction. During the strain-hardening phase, the differential modulus scales as a power-law with the stress K ∼ σ ν 1 ; a typical feature of structures with nonaffine behavior [24,[27][28][29]. Interestingly, the scaling seems to depend only on the volume fraction and is similar for all models.…”
mentioning
confidence: 83%